Pesan-pesan Dakwah dalam Bahasa Tutur - Hikmat, Hikmat (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2011)
Forwarding of The daâwah messagesÂ in oral language. Oral language in this context isÂ transmitted, trasacted and transformated from relevan values. Even if the message of daâwah in oral language is culture frame that eksist in community, but its posite not outsideÂ of principles: qulan sadidan, Balighan, maârufan, kariman, layyinan, dab qoulan maysuran, that the message od daâwah can be manual by people danÂ followed it, because daâI is a availableÂ person for people followed it all.